2019
DOI: 10.2217/cns-2019-0016
|View full text |Cite
|
Sign up to set email alerts
|

Utility of flouro-deoxy-glucose positron emission tomography/computed tomography in the diagnostic and staging evaluation of patients with primary CNS lymphoma

Abstract: Aim: To prospectively assess the clinical utility of pretreatment flouro-deoxy-glucose positron emission tomography/computed tomography (18F-FDG-PET/CT) in patients with primary central nervous system (CNS) lymphoma (PCNSL). Materials & methods: Patients with suspected/proven PCNSL underwent baseline whole-body 18F-FDG-PET/CT. Maximum standardized uptake value and tumor/normal tissue ratios were compared between CNS lymphoma and other histological diagnoses. Results: The mean maximum standardized uptake va… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
15
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 19 publications
(15 citation statements)
references
References 40 publications
(30 reference statements)
0
15
0
Order By: Relevance
“…However, some lesions visualized on MRI had no correlate on FDG PET ( 31 , 107 , 110 112 ) due to, e.g., small lesion size (usually <1 cm) and their pattern on MRI, such as disseminated presentation. Furthermore, leptomeningeal disease and eye involvement, diagnosed on CSF flow cytometry and vitreous aspirate, are usually not detectable on PET ( 31 ), due to small volume of FDG-avid disease or prominent FDG uptake in adjacent physiologic structures. This is also true for lesions in proximity to basal ganglia, which exhibit high physiologic FDG uptake.…”
Section: Pet Imagingmentioning
confidence: 99%
See 3 more Smart Citations
“…However, some lesions visualized on MRI had no correlate on FDG PET ( 31 , 107 , 110 112 ) due to, e.g., small lesion size (usually <1 cm) and their pattern on MRI, such as disseminated presentation. Furthermore, leptomeningeal disease and eye involvement, diagnosed on CSF flow cytometry and vitreous aspirate, are usually not detectable on PET ( 31 ), due to small volume of FDG-avid disease or prominent FDG uptake in adjacent physiologic structures. This is also true for lesions in proximity to basal ganglia, which exhibit high physiologic FDG uptake.…”
Section: Pet Imagingmentioning
confidence: 99%
“…The utility of whole-body FDG PET/CT for the staging and detection of lymphoma outside the brain has been corroborated in several studies. Indeed, FDG PET/CT has shown that about 4–10% of patients with suspected lymphoma confined to the brain have systemic involvement ( 31 , 117 ).…”
Section: Pet Imagingmentioning
confidence: 99%
See 2 more Smart Citations
“…There is increasing evidence to suggest that FDG-PET imaging may be more sensitive than a conventional CT of the chest, abdomen, and pelvis as well as bone marrow biopsies for detecting systemic disease in PCNSL ( 69 ). Recent prospective studies suggest a significantly higher FDG-uptake in CNS lymphomas (n=45) compared to other histologic diagnoses (n=23) ( 70 ). Similarly, other authors have suggested that metabolic PET imaging with agents such as FDG and 11 C-methionin shows promise as a predictive biomarker and early detection of recurrences ( 71 , 72 ).…”
Section: Nuclear Imaging and Positron Emission Tomography (Pet)mentioning
confidence: 99%